Motivations for the use and consumption of wildlife products - Thomas-Walters, L; Hinsley, A; Bergin, D; Doughty, H; Gaspar Verissimo, D; Et al. (Wiley, 2020)
The dominant approach to combating the illegal wildlife trade has traditionally been to restrict the supply of wildlife products. Yet conservationists increasingly recognize the importance of implementing demand‐side interventions that target the end consumers in the trade chain. Their aim is to curb the consumption of wildlife or shift consumption to more sustainable alternatives. However, there are still considerable knowledge gaps in understanding of the diversity of consumer motivations in the context of illegal wildlife trade, which includes hundreds of thousands of species, different uses, and diverse contexts. Based on consultation with multiple experts from a diversity of backgrounds, nationalities, and focal taxa, we developed a typology of common motivations held by wildlife consumers that can be used to inform conservation interventions. We identified 5 main motivational categories for wildlife use: experiential, social, functional, financial, and spiritual, each containing subcategories. This framework is intended to facilitate the segmentation of consumers based on psychographics and allow the tailoring of interventions—whether behavior change campaigns, enforcement efforts, or incentive programs—to the specific context in which they will be used. Underlining the importance of consumer research and collaborating with local actors is an important step toward promoting a more systematic approach to the design of demand reduction interventions.